Ludzie w zawieszeniu (Siergiej Lebiediew, Dzieci Kronosa) - Zywert, Aleksandra (Rusycystyczne Studia Literaturoznawcze, 2020)
In the novel The Goose Fritz, Sergei Lebedev puts the spotlight on the still-relevant problem of the history of Russian Germans, a question which adds depth to discussion about the complex past of the country. Russian Germans, as the author portrays them, live in a state of suspension, bearing a mark of foreignness in both Russia and Germany. Functioning almost from the very beginning between two totalitarian regimes (tsarist and then Soviet regimes on one side, and on the other, fascism), each of which forces people to divest themselves of their own past in favor of an identity aligned with the more “correct” politics of the time and place, Russian Germans have lost the memory of generations and remain “an uprooted people”. In this context, Lebedev’s story concerns human nature as such, as well as a problem of great importance for contemporary Russia: the status of the German minority and the prospect of their migration to Germany.